1997
DOI: 10.1007/s004180050116
|View full text |Cite
|
Sign up to set email alerts
|

Localization of vitronectin in the normal and atherosclerotic human vessel wall

Abstract: Vitronectin (Vn) regulates proteolytic enzyme systems, as well as cell migration and tissue remodelling. These processes have been implicated in the pathogenesis of atherosclerosis. In this study, the distribution of Vn antigen in apparently normal and atherosclerotic human blood vessels was evaluated. Normal and diseased vessels showed Vn immunostaining in the lamina elastica interna and externa, and in strand-like structures in the adventitia. In most of these instances, the Vn antigen appeared to be located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
1
34
0
1
Order By: Relevance
“…Furthermore, comparison of growth factor binding to the different VN isoforms revealed that multimeric forms of VN (predominantly present in the ECM and secreted by platelets) exhibit higher affinity than plasma VN for TGF-␤. Heparin-binding VN multimers are thought to be the major reactive forms of the adhesive protein in connective tissue or on cell surfaces and may become deposited in the vessel wall upon vascular injury or during aging (Dufourcq et al, 1998;Mullins et al, 2000;Preissner 1991;Van Aken et al, 1997). Thus, binding to VN can potentially increase the local concentration of a respective growth factor at the cell-ECM interface and thereby influences its functions.…”
Section: Vitronectin-tgf-␤ Interactionsmentioning
confidence: 99%
“…Furthermore, comparison of growth factor binding to the different VN isoforms revealed that multimeric forms of VN (predominantly present in the ECM and secreted by platelets) exhibit higher affinity than plasma VN for TGF-␤. Heparin-binding VN multimers are thought to be the major reactive forms of the adhesive protein in connective tissue or on cell surfaces and may become deposited in the vessel wall upon vascular injury or during aging (Dufourcq et al, 1998;Mullins et al, 2000;Preissner 1991;Van Aken et al, 1997). Thus, binding to VN can potentially increase the local concentration of a respective growth factor at the cell-ECM interface and thereby influences its functions.…”
Section: Vitronectin-tgf-␤ Interactionsmentioning
confidence: 99%
“…12 Immunohistochemical staining for PAI-1 was performed with a Histostain-Plus kit, Zymed Laboratories, as described previously. 15 Secondary antibody was biotinylated goat anti-rabbit IgG.…”
Section: Histological Analysesmentioning
confidence: 99%
“…Vitronectin is a multifunctional glycoprotein present in plasma, platelets, and the extravascular matrix. Like PAI-1, vitronectin is deposited at sites of disease or injury (15,16), where it binds multiple ligands, including collagens, fibrin, uPA receptor, integrins, and PAI-1 (17)(18)(19)(20)(21). Plasma vitronectin is in a closed conformation that does not interact with integrins.…”
mentioning
confidence: 99%